Dynamics System Analysis in Measuring English Language Performance - Adityo Adityo (ELITE Association Indonesia, 2020)
Measuring the performance of language is a challenge to the education system in every education level. In measuring the performance of language, the analysis should be conducted in each individual to find the best understanding of the learners’ real performance of language ability on language learning. Conventionally, the test evaluator is evaluating the achievement by using a one-time test to analyze the language achievement in a time-saving and simple evaluation. While the conventional evaluation method seems to be practical, the result of the evaluation is only revealing the language achievement on the day the test is administered by ignoring the dynamics of the language acquisition of the learners. the research is dealing with implementing a new method in understanding language acquisition of the performers. The research employs descriptive-quantitative method and gathering the data in a series of 4 times data collections by using specific task to the students in English department of UMM as the purposively selected subjects. Following the data collection, the analysis is conducted in a series of 4 analyses to show the ‘movement’ or the dynamics of the language performance and use.Based on the result, the research validates the dynamics system analysis as a new method of measuring language performance in detail.